(3haGI aGWeI GdRgQGA HfJ eMeO GdeUWai Udi Gddg Ydjg hSdes - (3eLghds ((3edG eMeO CZGehG Hf Ydjs)
(3ChdgG (B:s
(3bjd deG Jhaj CHjgG (B((3cPG(B) (3QShd Gddg Udi Gddg Ydjg hSde CTQa GdBHGA hSjO GdeQSdjf hSjO GdCUajGA hQShd ecI hGdHWMGA HbjJ PGgdI GdYbds
(3BNQgG (B:s
(3acja MGdfG ef HYOge (B*** (3SdefG CeQfG Edi NGdbfG , jaYd eG jTGA hjNJGQ (B*** (3Efg Ydi cd TjA bOjQs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJGQjNs